OP0302 MUCOSAL-ASSOCIATED INVARIANT T (MAIT)-CELL-DERIVED IL-17A AND IL-17F PRODUCTION IS IL-23-INDEPENDENT AND BIASED TOWARDS IL-17F. (June 2019) - Cole, Suzanne; Simpson, Catherine; Okoye, Remi; Griffiths, Meryn; Baeten, Dominique; Shaw, Stevan; Maroof, Ash
Abstract : Background: The requirement for IL-23 in driving IL-17A and IL-17F production in humans is incompletely understood. Preclinical data support IL-17F, together with IL-17A, as a key driver of chronic tissue inflammation. 1 MAIT cells, an innate-like T cell population, uniformly express RORγt but only a minority have been shown to produce IL-17A. 2 Dysregulation in frequency and function of MAIT cells has been associated with IL-17A-mediated inflammatory diseases, including PsA and AS. 3, 4 IL-17F production in MAIT cells remains largely unexplored. Objectives: To explore the importance of IL-23 signalling in MAIT cell-derived IL-17A and IL-17F production, examine the presence of MAIT cells in psoriatic lesional skin and assess the contribution of MAIT cell-derived IL-17A and IL-17F using in vitro models of skin inflammation. Methods: IL-17A and IL-17F production by MAIT cells was assessed by flow cytometry, ELISA, qPCR and CyTOF upon activation by anti-CD3/CD28 or fixed E. coli via MR1–presented riboflavin metabolites, with or without disease-relevant recombinant cytokines or an IL-23-neutralising antibody. RNAscope was utilised to observe MAIT cells in psoriatic lesional skin. MAIT cell supernatant, generated from FACS sorted activated MAIT cells, was cultured with normal human dermal fibroblasts (NHDFs) in the presence of IL-17-isoform-specific antibodies, including bimekizumab, a monoclonal antibody that potently and selectively neutralises both IL-17A and IL-17F. Results: Optimal MAIT cell IL-17A and IL-17F production occurred upon T cell receptor triggering with IL-12 and IL-18, independently of IL-23. IL-17F expression was greater at both gene and protein levels than IL-17A. The kinetics and threshold of activation for IL-17A and IL-17F suggest tighter regulation compared with other inflammatory cytokines, including IFNγ and TNF. Optimal MAIT cell IL-17A and IL-17F production requires monocytes, which contribute to IL-12 production upon IL-18 stimulation. MAIT cells were abundant in psoriatic lesional skin. NHDFs cultured with supernatant generated from activated MAIT cells produced inflammatory mediators IL-6, IL-8 and CCL2, which were reduced upon inhibition of either IL–17A or IL-17F, with optimal suppression achieved following dual neutralisation with bimekizumab. Conclusion: IL-17A and IL-17F can be produced from MAIT cells independently of IL-23, and contribute to inflammatory responses in NHDFs. These results support dual neutralisation of IL-17A and IL-17F as a complete and targeted approach to supress IL–17–driven inflammatory responses. Reference: [1] Glatt Ann Rheum Dis 2018;77:523–32, 2Dusseaux Blood 2011;117:1250–59, 3Menon Arthritis Rheumatol 2014;66:1272–81, 4Gracey Ann Rheum Dis 2016;75:2124–32 Acknowledgement: Funded by UCB Pharma. The authors would like to acknowledge Alexandra Webster MSc, of iMed Comms, an Ashfield Company, for editorial support that was funded by UCB Pharma in accordance with Good Publication Practice (GPP3) guidelines. The authors acknowledge Alvaro Arjona, PhD, of UCB Pharma, for publication and editorial support. Disclosure of Interests: Suzanne Cole Employee of: UCB Pharma, Catherine Simpson Employee of: UCB Pharma, Remi Okoye Shareholder of: UCB Pharma, Employee of: UCB Pharma, Meryn Griffiths Consultant for: UCB Pharma, Employee of: UCB Pharma, Dominique Baeten Shareholder of: UCB Pharma, Employee of: UCB Pharma, Stevan Shaw Employee of: UCB Pharma, Ash Maroof Shareholder of: UCB Pharma, Employee of: UCB Pharma